Olinciguat, an Oral sGC Stimulator, Exhibits Diverse Pharmacology Across Preclinical Models of Cardiovascular, Metabolic, Renal, and Inflammatory Disease - Zimmer, Daniel P.; Shea, Courtney M.; Tobin, Jenny V.; Tchernychev, Boris; Germano, Peter; Sykes, Kristie; Banijamali, Ali R.; Jacobson, Sarah; Bernier, Sylvie G.; Sarno, Renee; Carvalho, Andrew; Chien, Yueh-tyng; et al. (Frontiers in Pharmacology, 2020)
Nitric oxide (NO)-soluble guanylate cyclase (sGC)-cyclic 3’,5’ GMP (cGMP) signaling plays a central role in regulation of diverse processes including smooth muscle relaxation, inflammation, and fibrosis. sGC is activated by the short-lived physiologic mediator NO. sGC stimulators are small-molecule compounds that directly bind to sGC to enhance NO-mediated cGMP signaling. Olinciguat, (R)-3,3,3-trifluoro-2-(((5-fluoro-2-(1-(2-fluorobenzyl)-5-(isoxazol-3-yl)-1H-pyrazol-3-yl)pyrimidin-4-yl)amino)methyl)-2-hydroxypropanamide, is a new sGC stimulator currently in Phase 2 clinical development. To understand the potential clinical utility of olinciguat, we studied its pharmacokinetics, tissue distribution, and pharmacologic effects in preclinical models. Olinciguat relaxed human vascular smooth muscle and was a potent inhibitor of vascular smooth muscle proliferation in vitro. These antiproliferative effects were potentiated by the phosphodiesterase 5 inhibitor tadalafil, which did not inhibit vascular smooth muscle proliferation on its own. Olinciguat was orally bioavailable and predominantly cleared by the liver in rats. In a rat whole body autoradiography study, olinciguat-derived radioactivity in most tissues was comparable to plasma levels, indicating a balanced distribution between vascular and extravascular compartments. Olinciguat was explored in rodent models to explore its effects on the vasculature, the heart, the kidneys, metabolism, and inflammation. Olinciguat reduced blood pressure in normotensive and hypertensive rats. Olinciguat was cardioprotective in the Dahl rat salt-sensitive hypertensive heart failure model. In the rat ZSF1 model of diabetic nephropathy and metabolic syndrome, olinciguat was renoprotective and associated with lower circulating glucose, cholesterol, and triglycerides. In a mouse TNFα-induced inflammation model, olinciguat treatment was associated with lower levels of endothelial and leukocyte-derived soluble adhesion molecules. The pharmacological features of olinciguat suggest that it may have broad therapeutic potential and that it may be ideally suited for diseases that have both vascular and extravascular pathologies.